FRI0061 Multi-biomarker disease activity (MBDA) score and the 12 individual biomarkers in early rheumatoid arthritis patients relate differentially to clinical response and radiographic progression: results from the swefot trial. (23rd January 2014) - Hambardzumyan, K.; Saevarsdottir, S.; Bolce, R.; Forslind, K.; Ernestam, S.; Petersson, I.; Geborek, P.; Chernoff, D.; Haney, D.; Sasso, E. H.; van Vollenhoven, R. F.
Abstract : Background: In early rheumatoid arthritis (eRA), predictors of clinical response and of radiographic progression would be very useful for optimal targeting of available therapies. Individual biomarkers as well as combinations of biomarkers, such as the MBDA test, can be considered for these purposes. In the SWEFOT study, patients with eRA (symptom duration < 1 year) were started on methotrexate (MTX); at 3 months, responders (DAS28 ≤ 3.2) continued MTX monotherapy and were followed in regular care, whereas non-responders were randomized to receive either triple DMARD therapy or the addition of infliximab. Objectives: To study the MBDA score and the levels of the 12 individual biomarkers at baseline (BL) as predictors of clinical response at 3 months and radiographic progression at 1 year in eRA. Methods: Analyses were performed for patients from the SWEFOT trial who had BL and 3-month assessments of DAS28 (based on ESR), and the MBDA score and the 12 individual biomarkers at BL; and for a subset of patients who also had radiographs at BL and 1 year time-points (assessed using the Van der Heijde modified Sharp score [SvdH]). Patients with DAS28 > 3.2 at 3 months were considered clinical non-responders, and patients with a change in SvdH > 0 as radiographic progressors ("radiological non-responders"). Group comparisons of biomarkers and MBDA scores were performed by Mann-Whitney U test. Results: The results are summarized in the table below. Clinical non-responders had significantly higher BL values for CRP and IL-6 compared to responders. TNF-R1 and VCAM-1 were significantly lower for non-responders, while other biomarkers and the MBDA did not differ. The patients who progressed radiographically had, at BL, significantly higher MBDA scores, inflammatory biomarkers (CRP, SSA and IL-6), MMP-1, MMP-3 and TNF-R1, as well as a trend towards higher VEGF. Conclusions: In eRA patients treated initially with MTX, individual biomarkers at BL may help identify those patients who are less likely to achieve DAS28 ≤ 3.2 after 3 months of MTX therapy. In addition, the MBDA score and individual biomarkers at BL may identify patients at higher risk for radiographic progression during the first year of therapy. Disclosure of Interest: K. Hambardzumyan: None Declared, S. Saevarsdottir: None Declared, R. Bolce Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience, K. Forslind: None Declared, S. Ernestam: None Declared, I. Petersson: None Declared, P. Geborek: None Declared, D. Chernoff Shareholder of: Crescendo Bioscience, Consultant for: Crescendo Bioscience, D. Haney Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience, E. Sasso Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience, R. van Vollenhoven Grant/research support from: AbbVie, BMS, GSK, MSD, Pfizer, Roche, UCB, Consultant for: AbbVie, BMS, GSK, MSD, Pfizer, Roche, UCB